Testing for competition in banking: Behavioral evidence from Finland - Jukka Vesala (Bank of Finland, 1995)
Table of Contents: Acknowledgements 5 1 Introduction and background 11 1.1 Research methodology 12 1.1.1 Industrial organization, competition and efficiency 13 1.1.2 Oligopoly theory and tacit collusion 14 1.1.3 Shortcomings of the SCP 17 1.1.4 Review of studies testing for SCP in banking 21 1.1.5 NEIO-approach to studying competition 23 1.2 Deregulation and banking competition 26 1.2.1 Spatial model of banks' delivery capacity choices 26 1.2.2 Interpretation of model predictions 30 1.2.3 Banking competition after deregulation - international evidence 34 1.3 Competition policy issues for banking 37 1.4 Background facts on the Finnish banking sector 41 2 Competition tests based on empirical reduced form revenue equations 47 2.1 Testing for competition using reduced form revenue functions 48 2.2 Derivation of testable hypotheses 49 2.2.1 Monopolistic competition equilibrium without threat of entry 50 2.2.2 Monopolistic competition free entry (Chamberlinian) equilibrium 53 2.2.3 Static oligopoly equilibria 57 2.2.4 Summary of empirical hypotheses 58 2.2.5 Empirical reduced form revenue equations 59 2.3 Empirical implementation 60 2.3.1 Empirical model 60 2.3.2 Estimation and data 63 2.3.3 Results 64 2.3.3.1 Individual cross-section data 64 2.3.3.2 Pooled cross-section data 66 2.4 Conclusions 72 2.4.1 Competitive changes in Finnish banking 72 2.4.2 Previous studies 75 3 Testing for shifts in competitive conduct: a switching regression model 76 3.1 Motivation 76 3.2 Empirical model 79 3.2.1 Industry demand and supply relations 80 3.2.2 Empirical specification 82 3.3 Variables, estimation and results 87 3.4 Conclusions 92 4 Oligopolistic interdependence in bank loan and deposit markets 95 4.1 Foreword 95 4.2 Multimarket oligopoly 97 4.2.1 Implications of multimarket contact 97 4.2.2 General duopoly model 98 4.2.2.1 Direct and strategic effects 98 4.2.2.2 Characterization of strategic behaviour 101 4.2.3 Model of price setting duopolists - comparative statics 102 4.2.3.1 Linear demand and strategic complementarity 102 4.2.3.2 Equilibrium price effects 104 4.2.3.3 Equilibrium cross-market profit effects 110 4.3 Empirical behavioral equations ill 4.4 Data and variable specifications 116 4.5 Auxiliary cost and demand function estimations 120 4.5.1 Translog cost function model 120 4.5.2 Empirical measures of production economies 126 4.5.3 Production economies in Finnish banking - empirical results 131 4.5.4 Demand models for bank loans and deposit services 134 4.5.4.1 Demand for bank loans 134 4.5.4.2 Demand for deposit services 135 4.5.4.3 Estimation results 137 4.6 Behavioral equations: estimation and results 137 4.6.1 Average own market price coordination terms 139 4.6.2 Average cross-market price coordination terms 141 4.6.3 Bank group - specific price coordination terms 143 4.7 Summary and conclusions 145 5 Summary and joint conclusions 148 5.1 Price competition in the bank loan market and its evolution over time 149 5.2 Oligopolistic competition in bank loan and deposit markets 153 References 157 Appendices 167
URN:NBN:fi:bof-201408071719
Keywords: 330